2016
DOI: 10.1007/s12199-016-0528-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Aeromonas species in environmental water used in daily life in Okinawa Prefecture, Japan

Abstract: Objectives The genus Aeromonas is known to causes diseases such as food poisoning, sepsis, and wound infection. However, the mode of Aeromonas transmission from environment to humans is not clearly understood. To evaluate the health risks of Aeromonas spp. in environmental freshwater, the number, proportion and putative virulence factors of Aeromonas species were investigated in Okinawa Prefecture, Japan. Methods Environmental freshwater samples were collected from three dams, two springs and three private wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Bacterial pathogenesis can be initially revealed from the study of genes encoding these virulence factors, which can also be explored by studying the release mechanism of effector proteins. Studies have shown that A. veronii carries a large number of virulence factors [22], but since its discovery, the lack of recognition has resulted in the study of only known virulence factors as well as the isolation and identification of pathogenic strains [23]. The unknown virulence factors specifically involved in metabolic pathways, including those regulating gene networks, and controlling the pathogenicity of strains are rarely studied, which is increasingly becoming one of the obstacles to revealing the specific pathogenesis of A. veronii.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial pathogenesis can be initially revealed from the study of genes encoding these virulence factors, which can also be explored by studying the release mechanism of effector proteins. Studies have shown that A. veronii carries a large number of virulence factors [22], but since its discovery, the lack of recognition has resulted in the study of only known virulence factors as well as the isolation and identification of pathogenic strains [23]. The unknown virulence factors specifically involved in metabolic pathways, including those regulating gene networks, and controlling the pathogenicity of strains are rarely studied, which is increasingly becoming one of the obstacles to revealing the specific pathogenesis of A. veronii.…”
Section: Discussionmentioning
confidence: 99%
“…The mesophilic aeromonads are emerging as important pathogens in humans, among those mainly Aeromonas hydrophila , Aeromonas caviae and Aeromonas veronii bv. sobria have been predominantly found in clinical isolates (Miyagi et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Aeromonas hydrophila is the predominant species in freshwater and municipal drinking water supplies and in Nigeria lakes, the isolated species were A. hydrophila and A. sobria [12]. Several Aeromonas species having potential pathogenicity were also investigated in environmental water of Okinawa and A. veronii biovar sobria and A. jandaei were reported as the predominant species in dams, and A. hydrophila and/or A. eucrenophila were predominant in wells [13]. However, our limited number of isolates did not allow us to characterize the predominant species A. hydrophila and extended studies are certainly required.…”
Section: Sds-page Analysismentioning
confidence: 99%